Why Crowdfund? Motivations of Philippine-Based Project Owners and Backers - Vergara, Raymond Allan G.; Vergara, Kimberly Christie S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study examines why project owners and campaign backers participate in crowdfunding. It explores what motivates crowdfunding participants to seek funding or fund projects using a multiple-case study approach. This study finds that project owners are motivated to crowdfund because of financial and marketing benefits. On the other hand, campaign backers are motivated to fund campaigns because they want early access to products, participate in the community, and support the project for altruistic motives.